Remittances by emigrants: Issues and evidence - Andrés Solimano (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Remittances, after foreign direct investment, are currently the most important source of external finance to developing countries. Remittances surpass foreign aid, and tend to be more stable than such volatile capital flows as portfolio investment and international bank credit. Remittances are also an international redistribution from low-income migrants to their families in the home country. Worldwide, remittances are relatively concentrated in a group of developing countries: the top 20 recipient-countries of workers' remittances capture around 80 per cent of total remittances by workers to the developing countries. The three main source countries of remittances are the US, Saudi Arabia and Germany, while in terms of value, the three main recipient countries are India, Mexico and the Philippines.
Keywords: J30; G15; F22; 330; remittances; capital flows; development finance; Rücküberweisung (Migranten); Welt